Students’ Perception Regarding the Use of Google Translate for English Text Translation - Mastang, Mastang; Afifah, Afifah; Fatima, Fatima (Datokarama English Education Journal, 2024)
The use of digital tools in the learning process is common. Google Translate is used as an online translation tool to help the process of translating English texts. This research aims to discover the English Tadris Study Program students’ perception regarding using Google Translate to translate English texts at State Islamic University Datokarama Palu. The formulation of the problem is “How do the English Tadris Study Program students perceive the use of Google translate in translating English texts at State Islamic University Datokarama Palu?”. This research used a descriptive qualitative approach. The data were collected through questionnaires and interviews with 20 English Tadris Study Program batch 2020 students as research informants. The results showed that some students used Google Translate to translate English texts. The existence of Google Translate can help students with translation. Besides that, Google Translate helps students understand English texts. Some positive perceptions conveyed by the students from the results of the interview were about the use of Google translate, including easy access, help in knowing the pronunciation of a word, increasing vocabulary, and saving time in translating. However, there is a negative perception about using Google Translate, namely the accuracy of the translation results. The students argue that the translation results from Google Translate provide inaccurate translations, so it is recommended that translation results be rechecked using other translation media.